2023
DOI: 10.1039/d3ob00092c
|View full text |Cite
|
Sign up to set email alerts
|

Visible-light-induced C(sp3)−H thiocyanation of pyrazolin-5-ones: a practical synthesis of 4-thiocyanated 5-hydroxy-1H-pyrazoles

Abstract: A direct and aerobic approach to 4-thiocyanated 5-hydroxy-1H-pyrazoles via cross-coupling of pyrazolin-5-ones with ammonium thiocyanate is described. Under redox-neutral and metal-free conditions, a series of 4-thiocyanated 5-hydroxy-1H-pyrazoles could be easily...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…It is worth mentioning that all of the 4-substituted pyrazolones could be easily converted into 4-thiocyanated products in moderate to good yields (42–65%) in standard conditions 2. With simple operational protocols (without the need for a photocatalyst, as well as bases and strong oxidants), this transformation provides a practical and competitive method for the preparation of α-thiocyano 4-substituted pyrazolones …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning that all of the 4-substituted pyrazolones could be easily converted into 4-thiocyanated products in moderate to good yields (42–65%) in standard conditions 2. With simple operational protocols (without the need for a photocatalyst, as well as bases and strong oxidants), this transformation provides a practical and competitive method for the preparation of α-thiocyano 4-substituted pyrazolones …”
Section: Resultsmentioning
confidence: 99%
“…With simple operational protocols (without the need for a photocatalyst, as well as bases and strong oxidants), this transformation provides a practical and competitive method for the preparation of α-thiocyano 4-substituted pyrazolones. 29 Furthermore, we focused our attention on isoxazol-5-ones, which represent an important class of heterocycles, with several applications as bioactive compounds and versatile building blocks for further transformations. 30 We found Rose Bengal was more efficient compared with other photocatalysts, and the benzyl-substituted isoxazolone 7a could be converted into thiocyanation product 8a in a 51% yield by using 3 equiv of NH 4 SCN after 12 h at room temperature.…”
Section: The Journal Of Organic Chemistrymentioning
confidence: 99%
“…independently reported thiocyanation of N‐ aryl pyrazolone derivatives via radical pathway using K 2 S 2 O 8 in combination with NH 4 SCN which required overnight duration for completion of the reaction [7a,b] . Lei Wang and his team described similar methodologies for thiocyanation via visible light photocatalysis also took 12 hours for the completion [16] . Nevertheless, these strategies suffer from one or the other drawbacks such as use of oxidants, other co‐salts such as graphene oxide, KHCO 3 , NaClO 4 , high temperature and prolonged reaction times.…”
Section: Introductionmentioning
confidence: 99%
“…[7a,b] Lei Wang and his team described similar methodologies for thiocyanation via visible light photocatalysis also took 12 hours for the completion. [16] Nevertheless, these strategies suffer from one or the other drawbacks such as use of oxidants, other co-salts such as graphene oxide, KHCO 3 , NaClO 4 , high temperature and prolonged reaction times. Further advancement to these protocols is therefore required.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Owing to their significance various methods have been developed for synthesizing aryl thiocyanate's. [8,9,11] Whereas, alkyl thiocyanates are synthesized through cyanation of thiols, copper catalyzed directed thiocyanation of sulfonamides, [10d] nucleophilic substitution of alkyl halide, [10h] palladium catalyzed C(sp 3 )-H thiocyanation of 2-amino furans [10f] and photoinduced [10a] or electrochemical [10b] benzylic thiocyanation (Scheme 1B). [10] In a notable development Chen et al reported an AIBN-initiated benzylic C(sp 3 )-H thiocyanation with N-thiocyanatosaccharin.…”
mentioning
confidence: 99%